O governo novo e o projeto de privatização da educação em Minas Gerais - Martins, Ezequiel de Araújo (2022)
This research aimed to analyze the New Party-MG’s (2019-2022) neoliberal educational project, as well as its implementation process and collision with the principles of Democratic Management. This study’s relevance is justified by the current historical context in which several proposals for privatization of public education advance, a movement that has been promoting the retraction of social rights guaranteed by the Federal Constitution (1988). The 1970s’ economic crisis was a fertile ground for the neoliberal paradigm arousal, an ideology that establishes the idea of a minimum State as a model, restricting its field of action on the provision of security and justice. The New Party-MG’s government plan is based on the reproduction of neoliberal dogmas, thus promoting a privatization program, fiscal austerity, and State unaccountability on educational offer. From this perspective, the party has developed projects that transfer the responsibility of education to private initiative. These projects are based on the charter schools model, the creation of an awards and redistribution of resources based on results system, and partnerships with Public-Private institutions. During the period investigated by this research, a partnership was established with the Unibanco Institute, a philanthropic institution that offers educational management services in much of the national territory, and which has been criticized for centralization of decisions, and for its distance from the school reality. For this qualitative research development, a bibliographic study was carried out on proposals by neoliberal authors, such as: Ludwig von Mises, Friedrich Hayek, Milton Friedman, and Murray Rothbard. Sources on Minas Gerais educational management were also analyzed, such as: New Party’s government plan (“Freedom even late”); the Secretary of State of Minas Gerais Government official publications about “Somar Project”, “Holding Hands Projet”, “School Award in Transformation” and “Trails of the Future”; the Minas Gerais State Assembly Public Hearings’ videos, and press and social media publications. The data collected in this work allow us to conclude that New Party-MG government implemented a privatization program that has been developed on several areas, being characterized by the lack of dialogue with the public sector professionals, disrespecting state, and federal legislation, and thus promoting a managerial culture that clashes with democratic principles and values that guide the public management.